Blow up for a viscoelastic wave equation with space-time potential in Rn (2022)
In this paper, we consider the following wave equation: with space-time dependent potential, where the initial data have compact support. Under suitable assumptions on the nonlinear function f, the relaxation function g and the damping potential b, we obtain blow up results using the perturbed energy method.